1985
DOI: 10.1172/jci112236
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of aortic and carotid baroreflexes to heart rate control in man during steady state and dynamic increases in arterial pressure.

Abstract: We studied the contribution of carotid vs. extracarotid baroreceptors in control of heart rate in normal humans. We measured heart interval (HI) and arterial pressure during steady-state infusion of phenylephrine (PE). PE increased mean arterial pressure (MAP) by 13±2 mmHg (mean±SEM; n = 10) and thus stimulated both carotid and aortic baroreceptors. Neck pressure (NP) was applied during PE infusion to counter the increase in transmural carotid sinus pressure, thus leaving only aortic baroreceptors stimulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Experiments on selective (un)loading of aortic baroreceptors by simultaneous infusion of vasoactive substances and application of neck suction/ pressure to maintain a stable carotid sinus transmural pressure indicated that aortic baroreceptors are dominant in the baroreflex control of heart rate, with the carotid baroreceptors contributing only Ϸ30%. 28,29 In line with these observations, baroreflex control of heart rate in mainly determined by the distensibility of the aortic arch than of the carotid sinus. 30 In contrast, combined neck suction/pressure with nonpharmacological (de)loading of aortic baroreceptors indicate that carotid baroreceptors are the principal contributors to baroreflex control of heart rate.…”
Section: Timmers Et Al Sympathetic Control After Carotid Body Resectionmentioning
confidence: 53%
“…Experiments on selective (un)loading of aortic baroreceptors by simultaneous infusion of vasoactive substances and application of neck suction/ pressure to maintain a stable carotid sinus transmural pressure indicated that aortic baroreceptors are dominant in the baroreflex control of heart rate, with the carotid baroreceptors contributing only Ϸ30%. 28,29 In line with these observations, baroreflex control of heart rate in mainly determined by the distensibility of the aortic arch than of the carotid sinus. 30 In contrast, combined neck suction/pressure with nonpharmacological (de)loading of aortic baroreceptors indicate that carotid baroreceptors are the principal contributors to baroreflex control of heart rate.…”
Section: Timmers Et Al Sympathetic Control After Carotid Body Resectionmentioning
confidence: 53%
“…In any event, any effects of phenylephrine on the baroreflex itself is unlikely to have influenced our findings, since any such effect would be present during both the hypoxic and hypercapnic stresses. With regard to possible effects of phenylephrine on the baroreflexes, the doses of phenylephrine used in this study do not sensitize the arterial baroreceptors to graded levels of neck pressure (14).…”
Section: Discussionmentioning
confidence: 75%
“…7 Under these conditions, baroreceptor reflex impairments are transient rather than permanent, presumably because there is marked redundancy of baroreceptor afferents, particularly in the control of sympathetic nerve activity. 8 " 10 Thus, the loss of carotid baroreceptor input does not appear to cause a long-term impairment in baroreceptor reflex control of sympathetic vasoconstrictor outflow so long as the aortic baroreceptors remain intact.…”
Section: Discussionmentioning
confidence: 99%